2002
DOI: 10.1002/jsfa.1261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of previous chilled storage on rancidity development in frozen horse mackerel (Trachurus trachurus)

Abstract: Rancidity development during frozen storage (À20°C) of an underutilised medium-fatcontent fish species, horse mackerel (Trachurus trachurus), was studied. Special attention was given to the effect of previous chilled storage (0, 1, 3 and 5 days) on the quality of the frozen fish. For this, chemical (free fatty acid and conjugated diene contents; peroxide value, PV; thiobarbituric acid index, TBA-i; fluorescent compound formation) and sensory (rancid odour and taste) analyses were carried out. Hydrolytic rancid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
9
30
1
Order By: Relevance
“…However, in our study, the duration of the preliminary chilled storage did not produce significant effects (P40:05) on the FFA formation during subsequent frozen storage, this being in agreement with previous research (Aubourg et al, 2002).…”
Section: Lipid Hydrolysissupporting
confidence: 95%
See 2 more Smart Citations
“…However, in our study, the duration of the preliminary chilled storage did not produce significant effects (P40:05) on the FFA formation during subsequent frozen storage, this being in agreement with previous research (Aubourg et al, 2002).…”
Section: Lipid Hydrolysissupporting
confidence: 95%
“…Preliminary chilling time only exerted a significant effect (Po0:05) on rancidity in the case of fish specimens kept frozen for 1 and 2 months (Aubourg et al, 2002;Deng, 1978;Sankar & Viswanathan Nair, 1988;Undeland & Lingnert, 1999) while no effect was observed (P40:05) for specimens subjected to 4 months of frozen storage.…”
Section: Lipid Oxidationmentioning
confidence: 81%
See 1 more Smart Citation
“…The effect of previous chilling conditions (storage time, fish/ice ratio, room storage temperature) on the quality of frozen [47,48] and canned [49,50] fish has been demonstrated. According to the present results, application of slurry ice technology (alone or in combination with ozone) is found a promising technology to obtain higher quality fish products.…”
Section: Final Remarksmentioning
confidence: 98%
“…Reports have suggested that a very high ratio of citric acid to copper is needed (Castell et al 1965;Flider and Orthoeffer 1981;Aubourg et al 2003;). It is also tempting to suggest that the high NaCl concentration may have contributed to loss of chelating properties of the antioxidant.…”
mentioning
confidence: 99%